The Correlation between EFL Learners’ Motivation and Their Speaking Skills - Kurniawan, Andi; Salija, Kisman; Korompot, Chairil Anwar (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
The objective of this research is to determine whether there is any correlation between EFL learners’ motivation and their speaking skill of student in the second-semester academic year 2021-2022 of the English Education Study Program at the Faculty of Language and Literature State University of Makassar. This research is quantitative research with correlational study. The researcher used random sampling for this study and the total sample is 46 students. To gather the data, this study distributed questionnaire and conducted oral test to the students. Data were analyzed by correlating analysis using SPSS version 24. The findings showed that there was a high correlation between EFL learners’ motivation and their speaking skill. It is proved by the significance value is 0.000, which is lower than the level of significance (0.05) which means the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. In conclusion, there is a high correlation between EFL learners’ motivation and their speaking skill because the value is 0.690.